(untitled) - Yasuhiro, Sato (Tokyo, Japan, 2020)
The present book includes full-color illustrations of Jakuchu's lifework as well as other important paintings, arranged chronologically and accompanied by commentary from a variety of perspectives.
Keywords: Nghệ sĩ,Artists; Nhật Bản,Japan